Trends In Coloured Nursing Education - A.M. Venter (AOSIS, 1978)
Education as a selfgrowth process implies the potential successful adaptation to the world in which one lives; the latter becoming increasingly demanding through the expansion and growth of society as a whole. The Coloured nursing student of today, like all other students, lives in a fantastic era of technological advancement, industrialization, a continual struggle for academic achievement and above all the drive to achieve adjustment within the changing framework of society. The student must therefore be prepared to learn - which is a mental activity by means of which knowledge, skills, attitudes, and ideals are acquired, resulting in the modification of behaviour. The present-day nurse educator, therefore, not only has to be professionally and academically prepared for the educational task in nursing science but has to constantly update knowledge so as to keep abreast of the total interrelated picture of basic human science development. The success or failure of the student when she enters the professional world is an irrevocable reflection of the effectiveness of her teachers.